Manufacturing method of processed plastic material and processed plastic material

The laser welding and coating method addresses the inefficiencies of existing plastic surface modification techniques by providing an economical and environmentally friendly solution for achieving even and stable coatings on plastic materials.

JP7659882B2Active Publication Date: 2025-04-10TOKYO METROPOLITAN IND TECH RES INST
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020216863
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-25
Publication Date
2025-04-10
Estimated Expiration
2040-12-25

AI Technical Summary

Technical Problem

Existing methods for modifying plastic surfaces to enhance paint adhesion are costly, inefficient, and result in uneven coating due to high equipment costs and environmental concerns, while existing laser welding technologies only modify small portions or surfaces of engineering plastics without ensuring even and stable coating.

Method used

A method involving laser welding of a crystalline film to a plastic material, followed by coating, using specific laser parameters and coating agents to achieve even and stable coating, eliminating the need for chemical treatments and complex equipment.

Benefits of technology

The method allows for easy and inexpensive modification of plastic surfaces for stable coating, reducing environmental impact and improving paint adhesion, suitable for various industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659882000005
    Figure 0007659882000005
  • Figure 0007659882000006
    Figure 0007659882000006
  • Figure 0007659882000007
    Figure 0007659882000007
Patent Text Reader

Abstract

To provide a manufacturing method of a processed plastic material in which a plastic material can be inexpensively and easily modified so as to be able to be coated with a simple device and its surface can be modified so as to be able to be coated stably without unevenness, and the processed plastic material.SOLUTION: A manufacturing method of a processed plastic material 1 includes: a polymerization step of laminating a film 20 on a plastic material 10 to obtain a polymer; and an irradiation step of conducting laser irradiation from the film side in the polymer to integrate the plastic material and the film. The plastic material is preferably a plastic material formed using a polyacetal, a polycarbonate, a polyamide 6, a polyamide 66 or a polybutylene telephthalate as a raw material, and the film is preferably a crystalline film such as a polyethylene terephthalate film, a nylon film, a polypropylene film, or an ethylene-vinyl acetate copolymer film.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a processed plastic material, which can modify a plastic material easily and inexpensively using simple equipment to make it coatable, and which can modify the surface of the plastic material so that it can be coated evenly and stably, and to the processed plastic material. [Background technology]

[0002] Engineering plastics are used as metal replacement resins in the electrical and electronics and automotive fields, as well as in parts for everyday items. There is an increasing demand for these engineering plastics to be given decorative features by painting, but the poor adhesion of paint necessitates various pretreatments. Such pretreatments include mechanical treatments such as polishing, chemical treatments using a chromic acid mixture, and surface modification treatments such as plasma treatments and corona treatments. However, each of these treatment methods has problems such as uneven polishing, uneven processing, and waste liquid disposal, making it difficult to obtain a stable coated product. Specifically, mechanical processing can be difficult depending on the shape, and uneven polishing can occur depending on the polishing method, resulting in poor adhesion of the coating film. Surface modification treatments such as plasma processing and corona processing have the problem that the equipment costs are high, processing cannot be performed cheaply, and unevenness occurs even if processing is performed. Furthermore, there is a problem that poor adhesion occurs if painting is not performed immediately after processing. Chemical processing is a cheap method of processing, but since it uses chemicals such as chromic acid and perchloroethylene, there are problems with the environmental load such as waste liquid and odor discharged in the processing liquid and cleaning process. Furthermore, if the material is not properly cleaned in the cleaning process, there are cases where poor adhesion of the coating film occurs after painting. For this reason, it is difficult to obtain stable painted products, and there is a demand for the development of new pretreatment methods. As a technique for welding engineering plastics to various polymer materials, for example, Patent Document 1 proposes a technique for welding a polymer material used in a stent valve to fabric fibers containing polyethylene terephthalate, etc., using a laser. Patent Document 2 proposes laser welding polyacetal, etc. to polyethylene terephthalate, etc. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2018-504972 [Patent Document 2] Special Publication No. 2020-520336 Summary of the Invention [Problem to be solved by the invention]

[0004] However, the proposal in Patent Document 1 is to weld only a small portion of the polymer material, and does not modify the entire polymer material. Furthermore, the proposal in Patent Document 2 was to simply weld an engineering plastic such as polyacetal to another polymer material, but did not modify the entire surface of the engineering plastic, and therefore was still insufficient as a surface modification technology. In short, at present, there is no technology proposed yet for modifying the surfaces of plastic molded bodies of various shapes so that they can be coated, which can be done easily and inexpensively using simple equipment, and which can modify the surfaces so that they can be coated evenly and stably.

[0005] Therefore, an object of the present invention is to provide a method for producing processed plastic material, which can modify the surface of plastic material so that it can be coated easily and inexpensively using simple equipment, and which can modify the surface so that it can be coated evenly and stably, and to provide the processed plastic material. [Means for solving the problem]

[0006] As a result of intensive research into solving the above problems, the inventors noticed that it is possible to modify the surface of plastic materials by applying laser welding technology, and as a result of their intensive research, they have completed the present invention. That is, the present invention provides the following inventions. 1. A polymerization process in which a film is laminated onto a plastic material to obtain a polymerized product; and an irradiation step of irradiating the polymer with a laser from the film side to integrate the plastic material and the film. 2. The above plastic material is 2. A method for producing a processed plastic material according to claim 1, which is a plastic material formed using polyacetal, polycarbonate, polyamide 6, polyamide 66 or polybutylene terephthalate as a raw material. 3. The method for producing a processed plastic material according to 1 or 2, wherein the film is a crystalline film. 4. The crystalline film is 4. The method for producing a processed plastic material according to claim 3, wherein the processed plastic material is a polyethylene terephthalate film, a nylon film, a polypropylene film, or an ethylene-vinyl acetate copolymer film. 5. The energy of the laser used in the above laser irradiation is 0.35 to 1.0 J / mm 2 5. The method for producing a processed plastic material according to any one of 1 to 4, wherein irradiation is carried out so as to obtain the above-mentioned. 6. The method for producing processed plastics according to any one of 1 to 5, further comprising a coating step of applying a coating agent to the surface of the film after completion of the irradiation step, followed by drying. 7. A processed plastic material in which a film is attached to the surface of a plastic material via a welded layer formed by welding the two together, wherein the thickness of the welded layer is 30 to 70 μm and Sa (surface roughness) is 3 to 100 μm. 8. The processed plastic material according to 7, further comprising a coating layer on the surface of the film. Effect of the Invention

[0007] According to the method for producing processed plastic material of the present invention, the plastic material can be modified easily and inexpensively with simple equipment to make it coatable, and the surface can be modified to make it coatable evenly and stably. Furthermore, the processed plastic material of the present invention can be easily coated on its surface with various types of paint. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is an exploded perspective view showing a jig used in the manufacturing method of the present invention. [Diagram 2] FIG. 2 is a side view that illustrates one embodiment of the processed plastic material of the present invention. [Diagram 3] 3(a) to (k) are enlarged photographs (drawing substitute photographs) of the surfaces of the processed plastic materials obtained in Examples 1 to 11, respectively. [Figure 4] FIG. 4(a) to (d) are enlarged photographs (drawing substitute photographs) of the processed plastic materials obtained in Examples 12 to 15, respectively. [Diagram 5] FIG. 5(a) to (d) are enlarged photographs (photographs substituting drawings) of the processed plastic materials obtained in Examples 16 to 19, respectively. [Figure 6] FIG. 6(a) to (d) are enlarged photographs (photographs substituting drawings) of the processed plastic materials obtained in Examples 20 to 23, respectively. [Figure 7] FIG. 7 is a chart showing the relationship between wavelength and transmittance of the film. [Explanation of symbols]

[0009] 1 processed plastic material, 10 plastic materials, 20 film, 30 welding layer, 40 coating layer DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in further detail below, but the present invention is not limited thereto. First, the method for producing the processed plastic material of the present invention will be described, and then the processed plastic material of the present invention will be described. <Manufacturing method> The method for producing processed plastic material of the present invention can be carried out by carrying out a polymerization step in which a film is overlaid on a plastic material to obtain a polymerized product, and an irradiation step in which a laser is irradiated from the film side of the polymerized product to integrate the plastic material and the film. In the present invention, in addition to the above steps, a coating step of applying a coating agent to the film surface may be carried out. Hereinafter, first, materials that can be used in this embodiment will be described, and then each step will be described.

[0011] [Plastic materials] The plastic material used in the present invention includes plastic materials known as engineering plastics, which have excellent strength and heat resistance. Specifically, plastic materials formed using raw materials such as polyacetal, polycarbonate, polyamide 6, polyamide 66, or polybutylene terephthalate can be preferably used. The plastic material may be made only of the above raw materials, but may also contain various additives that are usually used in engineering plastics within the ranges usually used. The plastic material used in the present invention may have various shapes, including molded bodies having a predetermined shape such as a plate, a tetrahedron, a sphere, an elliptical sphere, a cone, etc. The color of the plastic material is preferably a color that easily absorbs laser energy, and is more preferably low-brightness black or a dark color close to black. 〔film〕 The film used in the present invention is preferably a crystalline film having a melting point. Examples of the crystalline film used in this case include polyethylene terephthalate film, nylon film, polypropylene film, polyethylene film, and ethylene-vinyl acetate copolymer film. Since the crystalline film needs to be welded at the contact portion with the plastic material, it is preferable that the energy of the laser light used can sufficiently reach the contact portion with the plastic material, and more preferably, it has a sufficient transmittance for the laser light. For example, when the laser light used is a blue diode laser (wavelength 445 nm), the transmittance for wavelengths of 440 nm to 500 nm is preferably 80% or more, and more preferably 85% or more. That is, the crystalline film means a film having a transmittance equal to or higher than a predetermined value and a melting point, regardless of the above examples. The crystalline film may have a color, and includes a film colored in black or the like, so long as it has the above transmittance. The crystalline film may contain various additives, and may have functions such as antistatic properties and ultraviolet absorbing properties. The thickness of the film is not particularly limited, but is preferably 15 to 100 μm.

[0012] [Coating Agent] As the coating agent, polyester resin paint, acrylic urethane resin paint, epoxy resin paint, acrylic resin paint, silicone resin paint, fluororesin paint, etc. can be used. [Other ingredients] In the present invention, in addition to the above-mentioned raw materials, various materials can be used without departing from the spirit of the present invention.

[0013] [Polymerization process] In this process, the plastic material and the film are laminated together so that no air bubbles are trapped between them. Here, "no air bubbles" means that the film is in close contact with the surface of the plastic material, with no air layer between them. Therefore, the polymerized material means that the film is in close contact with the surface of the plastic material. However, in the polymerized material, the film does not need to be in close contact with the entire surface of the plastic material, and the film may be integrated with the entire surface of the plastic material by repeating the polymerization step and the irradiation step partially and integrating the film multiple times. In particular, when using a plate-shaped plastic material as described below, it is possible to obtain a polymerized material by adhering the film to the entire surface of the plastic material in one operation, but if the plastic material has a complex shape, it may not be possible to adhere the film to the entire surface of the plastic material in one operation. In such a case, it is necessary to repeat the operation multiple times as described above. In this step, for example, when the plastic material is a plate-shaped body, the jig shown in FIG. 1 can be used to overlap the plastic material and the film. The jig 101 shown in FIG. 1 has a lower half 110 having an opening 111 in the center and an upper half 120 having an opening 121. The openings 111 and 121 are the same size. The lower half 110 and the upper half 120 are each rectangular, and are provided with connecting parts 130 at the four corners for tightly fixing the two halves. The connecting parts 130 can be formed by using any member having a mechanism for tightly connecting two members of this type so as to be detachable, without any particular restrictions, but in this embodiment, it is formed by using a fastening member that can be screwed (screwed). In addition, the lower half 110 and the upper half 120 are provided with linear convex parts 113, 123 for clamping around the openings 111, 121. The plastic material A and the film B can be clamped by these convex parts 113, 123. In this process, there are no particular limitations on the method of overlapping as long as the plastic material and the film can be adhered to each other. The film can be pressed against the surface of plastic materials of various shapes using various known tools to form an overlapping state, and then the process can proceed to the next irradiation process.

[0014] [Irradiation process] The irradiation process is a process of irradiating the polymer film with a laser. Since the laser can increase the energy density per area, it can bring plastic into a molten state in a short irradiation time and over a small area, making it a very effective method for resin welding. In the present invention, the laser used for the above-mentioned laser irradiation is not particularly limited as long as the wavelength of the irradiated laser can promote welding between the plastic material and the film, but it is preferable to select the wavelength of the laser light that can irradiate the laser so that the energy falls within the energy range of the laser described below. In addition, if the wavelength is too short, it will not transmit through the film and will not be able to promote welding, so it is preferable to use a laser that includes a wavelength that transmits through the above-mentioned film (preferably a wavelength with a transmittance of 85% or more as shown in Figure 7). As an example, it is preferable to use a laser that includes a wavelength of 445 nm. Furthermore, the irradiation range (area) of the laser irradiation is preferably such that the laser spot diameter is 0.1 to 0.5 mm and the irradiation interval is 0.1 to 1.0 mm. However, in the present invention, the laser energy (the laser energy irradiated to one location) is a more important concept, and it is preferable that the energy is 0.35 to 1.0 J / mm 2 It is preferable to irradiate so that the irradiation amount is 0.35 to 0.80 J / mm 2 It is more preferable to irradiate so that the irradiation is performed so that the irradiation intensity is 0.40 to 0.55 J / mm 2 If the irradiation is performed below the lower limit of this range, the welding may be insufficient, whereas if the irradiation is performed above the upper limit, the design of the surface of the processed plastic material may be adversely affected. The energy during laser irradiation is calculated using the following formula. Laser irradiation energy: E=P / (Sp × V) E: Energy (J / mm 2 ), P: Laser power (W), Sp: Spot diameter (mm) V: Speed ​​(mm / s) The laser output is preferably 0.1 to 5 W, more preferably 0.1 to 4 W, and most preferably 0.1 to 2.5 W. For the same energy, the lower the laser irradiation speed, the better the weldability, and the speed is preferably 6000 mm / min or less, more preferably 4000 mm / min or less, and most preferably 3000 mm / min or less.

[0015] [Coating process] The coating process is a process in which the processed plastic material in which the plastic material and the film have been integrated through the irradiation process is further coated with the coating agent, and after coating is completed, the processed plastic material is dried to obtain a processed plastic material with a coating layer formed on the surface. The coating method is not particularly limited, and methods such as bar coater, brush coating, roller brush coating, air spray, and airless spray can be used to coat the surface of the film layer formed by integrating the above films. The drying can be carried out by using a method such as natural drying, forced drying, heat drying, etc. In this case, the drying temperature and drying time in the case of heat drying are not particularly limited as long as the coating layer is cured. The amount of the coating agent applied is preferably such that the thickness of the coating layer formed is 5 to 100 μm.

[0016] [Other steps] In the present invention, in addition to the above-mentioned steps, other steps can be carried out without departing from the spirit of the present invention.

[0017] <Processed plastic materials> The processed plastic material of the present invention is a processed plastic material obtained by the above-mentioned manufacturing method of the processed plastic material of the present invention. One embodiment of the processed plastic material of the present invention will be described with reference to Fig. 2. The processed plastic material 1 shown in Fig. 2 is a processed plastic material in which a film 20 is integrated onto a surface of a plastic material 10 via a welding layer 30 formed by welding the two together. In this embodiment, a coating layer 40 is provided on the surface of the film 20. 2, the thickness and shape of the plastic material 10, and the thicknesses of the film 20 and the welding layer 30 are each shown diagrammatically, but the thickness and shape of the plastic material 10 are not particularly limited and may be any desired thickness and shape. The thickness of the film 20 is the same as the thickness of the film described in the above-mentioned manufacturing method. The thickness of the coating layer is also as described in the above-mentioned manufacturing method. The thickness of the above-mentioned welding layer is 30 to 70 μm, and preferably 30 to 60 μm. If the thickness is less than 30 μm, welding is insufficient and a problem occurs in which the film peels off, and if it exceeds 70 μm, the strength and heat resistance of the plastic material are impaired, so it is necessary to keep the thickness within the above range. The adhesive layer has a surface roughness Sa (arithmetic mean surface roughness) of 3 to 100 μm, preferably 30 to 70 μm. If the surface roughness is less than 3, the film is likely to peel off, and if it exceeds 100, the film surface becomes uneven, and the effect of improving the coatability of the plastic material cannot be obtained. Incidentally, Sa can be measured by a known method, but preferably, it can be calculated by measuring using a microscope according to a conventional method and taking the average value. Measurement equipment for Sa: Laser microscope (model: LEXT OLS4000, manufactured by Olympus Corporation)

[0018] [Other components] In the present invention, in addition to the above-mentioned components, other components can be added without departing from the spirit of the present invention.

[0019] [Effects and uses] Since the processed plastic material of the present invention is constructed as described above, it has the following effects. While paints suitable for plastic materials such as polyacetal, which is a difficult-to-adhere material, are still in the development stage and have not yet been commercially available, existing paints can be used to apply the material well, making it possible to produce plastic products with a variety of designs. In addition, there are cases where painting is done by chemical treatment, but if the material is not thoroughly cleaned in the cleaning process, there is a problem of difficult handling, such as poor adhesion problems after painting. The manufacturing method of the present invention can obtain processed plastic materials by the simple operation of laser irradiation, making handling easy and eliminating the need for a cleaning process, reducing adhesion problems compared to chemical treatment, and also reducing the environmental burden because no chemicals are used. Furthermore, if a functional film is used as the film to be welded, it is possible to add value, such as antistatic and ultraviolet protection. The manufacturing method and processed plastic material of the present invention are useful because they can produce stable coated products in the current situation where the use of design features for so-called engineering plastics such as polyacetal is on the rise. For example, they are expected to be used in various industrial fields such as decorative items such as buttons related to apparel, and exteriors and parts of home appliances.

[0020] The present invention is not limited to the above-described embodiment, and various modifications are possible without departing from the spirit of the present invention. EXAMPLES

[0021] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these in any way. [Examples 1 to 11] The following steps were carried out to obtain processed plastic materials of the present invention (Examples 1 to 11). The obtained processed plastic materials were evaluated for performance. (Polymerization process) First, using the apparatus shown in Figure 1, a polyacetal (hereinafter referred to as POM; product name "POM (black)" manufactured by Standard Test Piece Co., Ltd.) plate and a polyethylene terephthalate (PET) film (product name "Lumirror S10" manufactured by Toray Industries, Inc.) were stacked together while taking care not to trap air bubbles between them to obtain a polymerized material. (irradiation process) The obtained polymer was irradiated with a laser from the film side using a laser irradiator (product name "FABOOL Laser Mini" manufactured by smartDIYs Co., Ltd.) with the following conditions, with the irradiation energy being the conditions shown in Table 1. After the laser irradiation, the surface was observed. Laser Conditions: Laser Type: Laser Diode Laser wavelength: 445 nm Laser spot diameter: 0.2 mm Laser power: 0.18~3.5 W Pulse output: 0.18~0.35 W: 122 Hz, 0.36~1.2 W: 489 Hz, 0.37~3.5 W: 3.9 kHz Speed: 100~8000 mm / min Irradiation interval: 0.1 to 1.0 mm Laser focal length: 3mm [Table 1] The processed plastic materials obtained in Examples 1 to 11 were subjected to surface observation under a microscope. The results are shown in Fig. 3(a) to (k) ((a) shows Example 1, (b) shows Example 2, (c) shows Example 3, (d) shows Example 4, (e) shows Example 5, (f) shows Example 6, (g) shows Example 7, (h) shows Example 8, (i) shows Example 9, (j) shows Example 10, and (k) shows Example 11). The surface observation was performed by visually observing the surface magnified under a microscope (magnification 50 times). As a result of the surface observation, the processed plastic materials obtained in Examples 1 and 2 had severe unevenness and cracks on the surface, and holes were formed in the film. In the processed plastic materials of Examples 3 to 11, it can be seen that the unevenness of the surface decreases as the energy value decreases, and the melting of the PET film is improved.

[0022] [Examples 12 to 15] Next, under the conditions shown in Table 2, the energy values ​​were set to 0.70, 0.60, 0.53, and 0.47 J / mm 2 A processed plastic material was obtained in the same manner as in Example 1, except that the energy value was changed to 0.5 J / mm. Photographs of the obtained processed plastic material were taken with an optical microscope (Microscope, product name "VHX-500", manufactured by Keyence Corporation) and cross-sections were observed. The results are also shown in Table 2 and FIG. 4. As is clear from these results, when the energy value was high, the film broke and the POM eluted into the surface layer. On the other hand, when the energy value was 0.5 J / mm, 2 It was confirmed that the elution of POM was suppressed at this temperature. The resulting processed plastic material was subjected to the following coating process to form a coating layer. (Coating process) The paints used were a one-component polyester resin paint (product name "UV Clear UT049ASGK Gray" manufactured by Toho Kaken Kogyo Co., Ltd.) that has good adhesion to PET film, and a two-component acrylic urethane resin paint (product name "Nytec Nitko N-7 Gray Glossy" manufactured by Musashi Paint Co., Ltd.) The coating method used was the bar coater method, and the bar coater used was No. 75 (manufactured by AS ONE Corporation). The coating adhesion of the resulting processed plastic material having a coating layer was evaluated by a cross-cut test. The cross-cut test was performed in accordance with JIS K 5600-5-6:1999 General test methods for paints - Part 5: Mechanical properties of coatings - Section 6: Adhesion (cross-cut method). The cut interval was 2 mm, and the number of squares was 25. The results of the cross-cut test are shown in Table 2. As is clear from the results shown in Table 2 and Figure 4, the film was well welded in all cases, and the adhesion of the coating layer was good. In addition, the energy values ​​were 0.41, 0.38, and 0.31 J / mm 2 The processed plastic materials (Examples 15a to 15c) obtained in the same manner as in Example 11 except that the irradiation energy was changed to 1000 MPa were also coated in the same manner and subjected to a cross-cut test. The results are shown in Table 2. In Example 15c, the film peeled off, and evaluation in the cross-cut test was impossible. This shows that if the irradiation energy is too low, the welding of the film is not completed satisfactorily. [Table 2]

[0023] [Examples 16 to 19] A processed plastic material was obtained in the same manner as in Example 1, except that laser irradiation was performed under the conditions shown in Table 3. Microscope photographs of the obtained processed plastic material were taken and cross-sections were observed. The results are also shown in Table 3 and Figure 5. The obtained processed plastic material was subjected to a coating process similar to that of Example 12 to form a coating layer. The adhesion of the coating film of the obtained processed plastic material having a coating layer was evaluated by a cross-cut test similar to that of Example 12. The results are shown in Table 3. As is clear from the results shown in Table 3 and Figure 5, at energy values ​​of 0.76 and 0.60 J / mm 2 0.47 J / mm 2 The adhesion of the coating layer was better in Example 19, where the energy value was lower. This is thought to be because the lower the energy value, the less likely the film would break or the POM would leach out onto the surface layer. In addition, the energy values ​​were 0.41, 0.38, and 0.31 J / mm 2 The processed plastic materials (Examples 19a to 19c) obtained in the same manner as in Example 11 except that the irradiation energy was changed to 1000 MPa were also coated in the same manner and subjected to a cross-cut test. The results are shown in Table 3. As shown in Table 3, in Example 19c, the film peeled off, and evaluation in the cross-cut test was impossible. This shows that if the irradiation energy is too low, the welding of the film is not completed satisfactorily. [Table 3]

[0024] [Examples 20 to 23] Energy value: 0.47J / mm 2 A processed plastic material having a coating layer formed thereon was obtained in the same manner as in Example 16, except that the laser power and speed conditions were changed to those shown in Table 4. A cross-cut test was carried out on the obtained processed plastic material in the same manner as in Example 16. The results are shown in Table 4 and Figure 6 ((a) shows Example 20, (b) shows Example 21, (c) shows Example 22, and (d) shows Example 23, respectively). As is clear from the results shown in Table 4 and FIG. 6, a lower output and a lower speed are preferable, and a coating layer with better adhesion can be obtained. [Table 4]

[0025] [Test Example] The adhesion of the coating layer was compared between the processed plastic material obtained in Example 23 and a processed plastic material obtained by pretreating the plastic material using a conventional pretreatment method (solvent degreasing, surface polishing, chemical treatment) and then forming a coating layer. As the coating agent, both a one-component polyester resin paint and a two-component acrylic urethane resin paint were used. The general pretreatment methods were as follows: Solvent degreasing: The surface of the plastic material was degreased by wetting it with ethanol and wiping it off. Surface polishing: The surface of the plastic material was polished using abrasive paper #400. Chemical treatment: Using a mixed solution of sulfuric acid and phosphoric acid, the plastic material was immersed in the mixed solution at 40°C for 10 minutes to modify the surface of the plastic material. Evaluations were conducted on initial adhesion and secondary adhesion after long-term durability tests (chemical immersion tests). Each was evaluated by conducting a cross-cut test. For the chemical immersion test, the processed plastic material with the coating layer formed was immersed in petroleum benzene for 15 minutes, and then left to stand at room temperature for 15 minutes, with four sets of these being conducted. In terms of initial adhesion, after solvent degreasing and surface polishing, all paints showed poor adhesion, with a classification of 5. After chemical treatment and laser welding (the product of the present invention), the polyester resin-based paint showed a classification of 0, and the acrylic urethane resin-based paint showed good results, with a classification of 0 or 1. The chemical immersion test was carried out on the chemically treated product and the product of the present invention, which showed good initial adhesion. For both substrates and paints, the adhesion was good, with a classification of 0. In addition, the cross-cut test showed good results, with both being classified as 0 or 1. From these results, it can be seen that the processed plastic material obtained by the manufacturing method of the present invention can obtain coating film adhesion equal to or better than that obtained by chemical treatment, and since there is no need to handle hazardous materials such as acid, no special equipment or facilities are required as long as there is a laser irradiator, and no special treatment is required for waste disposal, so that the plastic material can be modified simply and easily to obtain a processed plastic material with good coating properties. In addition, in order to confirm materials that can be used as the above-mentioned film in the present invention, the relationship between transmittance and wavelength was measured for each of polyethylene film (LDPE, manufactured by Ube Film Co., Ltd.), polypropylene film (PP, manufactured by AS ONE Corporation), polyethylene terephthalate film (PET), polyvinyl chloride film (PVC, manufactured by Achilles Corporation), and polyphenylene sulfide (PPS, manufactured by AS ONE Corporation) using a spectrophotometer (U-4100 spectrophotometer). Each film used was a commercially available product with a thickness of 50 μm. The results are shown in FIG. 7. From the results shown in FIG. 7, the polyethylene film, polypropylene film, polyethylene terephthalate film, and polyvinyl chloride had a transmittance of 85% or more for wavelengths of 440 nm or more.

Claims

1. a polymerization step in which the film is laminated on the plastic material in close contact with each other without trapping any air bubbles between them to obtain a polymer; and an irradiation step of irradiating the entire overlapping surface of the polymer with a laser from the film side to integrate the plastic material and the film, The film is a crystalline film, The irradiation step includes: The laser irradiation interval is set to 0.1 to 1.0 mm. The laser irradiation energy E of the laser used in the above laser irradiation is calculated by the following formula, and the irradiation energy E is 0.35 to 0.80 J / mm 2 Irradiation is performed so that A method for producing engineered plastic materials. Formula: Laser irradiation energy: E = P / (Sp x V) E: Energy (J / mm 2 ), P: laser power (W), Sp: spot diameter (mm), V: speed (mm / s)

2. The resulting processed plastic material is integrated with the plastic material and the film via a welded layer formed by welding, 2. The method for producing processed plastic materials according to claim 1, wherein the irradiation step is carried out so that the thickness of the welding layer is 30 to 70 μm and the surface roughness Sa is 3 to 100 μm.

3. 2. The method for producing processed plastic materials according to claim 1, wherein the laser used in the irradiation step is a laser having a wavelength of 445 nm.

4. The plastic material is It is a plastic material made from polyacetal, polycarbonate, polyamide 6, polyamide 66, or polybutylene terephthalate. A method for producing the processed plastic material according to claim 1.

5. The crystalline film is Polyethylene terephthalate film, nylon film, polypropylene film, or ethylene-vinyl acetate copolymer film. A method for producing the processed plastic material according to claim 1.

6. Further, after the irradiation step, a coating step is provided in which a coating agent is applied to the surface of the film and then dried. A method for producing the processed plastic material according to claim 1.

7. It is made of a polymer formed by overlapping a plastic material and a film, The plastic material is a plastic material formed using polyacetal, polycarbonate, polyamide 6, polyamide 66, or polybutylene terephthalate as a raw material, The polymer is formed by integrating the plastic material and the film through a welding layer formed on the entire overlapping surfaces of the two materials, The processed plastic material has a thickness of the welding layer of 30 to 70 μm and a surface roughness Sa of 3 to 100 μm.

8. 8. The processed plastic material according to claim 7, further comprising a coating layer on the surface of the film.

Citation Information

Patent Citations

  • Decorative panel and production thereof

    JP1996072202A

  • Joining method of thermoplastic resin molded body and film, and composite molded body

    JP2003251698A

  • Laminated sheet and method of manufacturing laminated sheet

    JP2010137368A

  • Resin welding method

    JP2011240585A

  • Method for manufacturing composite materials by transmission laser welding

    JP2011529809A